GAMBARAN BODY IMAGE SALES PROMOTION GIRL OTOMOTIF - Sumi Lestari; Nadya Marenti Lumbanraja (Jurnal Sains Psikologi, 2018)
The purpose of this study is to know the body image of automotive sales promotion girl (SPG). This qualitative research is using phenomenology approach. Determination of research subjects based on purposive sampling technique. Subjects in this study amounted to 3 women who have or are in contract as automotive SPG. Data collection methods are using interview and observation, with interactive analysis model of Miles and Huberman‘s data analysis techniques, based on 5 body image dimensions of Cash & Pruzinsky (2002). The results showed that the three subjects have positive body image. Based on the five dimensions of Cash and Pruzinsky (2002)’s body image, the subjects focus on their overall performance as automotive sales promotion girl, ranging from the efforts to maintain the physical appearance as automotive SPG. Then, the body part that makes the subjects satisfied also the ideal shape as coveted the automotive SPG in general, and the size of the subjects is maintained to always be proportional as an automotive SPG.Kata Kunci: body image, metode kualitatif, sales promotion girl otomotifDOI: http://dx.doi.org/10.17977/um023v7i22018p155